PKM Pelatihan Teknik Pemenuhan Tujuan SDGs bagi Guru di Kabupaten Pangkep Provinsi Sulawesi Selatan - Lu'mu Lu'mu; Ruslan Ruslan (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract: This community service aims to educate Padanglampe MA teachers through technical training to fulfill the 17 SDGs goals. This service was carried out in Pangkep Prov. South Sulawesi. The training methods used were (1) lectures, questions and answers, and discussions; (2) Independent work and group work; (3) a presentation on participants' understanding of the 17 SDGs objectives. Based on the results of the evaluation at the end of this community service activity, it is known that overall participants who have attended this training understand enough about the techniques for fulfilling the 17 SDGs goals. Based on the results of the evaluation we conducted by discussing directly with the participants, it turns out that 92% of them already know very well about the methods or techniques for fulfilling the 17 SDGs goals in Pangkep Regency, Prov. South Sulawesi. Furthermore, 8% of the other participants did not fully understand how to carry out activities in order to accelerate the fulfillment of the 17 SDGs goals.